Accurate measurement of instantaneous values of voltage, current and power for power electronics circuits - Tung-Hai Chin; Nakano, M.; Hirayama, T. (PESC 98 Record. 29th Annual IEEE Power Electronics Specialists Conference (Cat. No.98CH36196), 1998)
For power electronics circuits, such as inverter circuits, the measurement of the instantaneous average value of the output voltage is rather troublesome and has never been undertaken in a rigorous sense. However, it becomes important when the inner states of the load connected to the inverter have to be calculated using the quantities of the load terminal voltages and currents, such as in the case of the vector control of induction motors without speed sensors. This paper tries to give an accurate measuring method for this voltage. The voltage cluster from the inverter is integrated every half period of the switching. Then the output of the integrator will be reset to zero after its volt-second value has been detected digitally. Two groups the circuits take the alternative operation. As the concerning subject, the measurement of the instantaneous current and power has also been discussed.